The Effect of Counseling on Student Behavior in Preventing Caries of the Permanent First Molars at Hidayatullah Islamic Elementary School and Al-Fath Islamic Boarding School Kendari City - Erfiani, Mery; Tasnim, Tasnim; Sunarsih, Sunarsih (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: Counseling is an educational activity carried out by giving messages, instilling confidence, so that people are not only aware, know and understand but are also willing and able to make recommendations that have to do with health. Health education is a combination of various activities and opportunities based on learning principles to achieve a situation where individuals, families, groups, or society as a whole want to live healthy, knowhow and do what can be done individually or in groups and receive help. Method: This research is a quantitative research type with a pre-experimental design. This research will be carried out at Hidayatullah Islamic Elementary School and Al-Fath Islamic Boarding School Kendari City. The population is Hidayatullah Islamic Elementary School students, Kendari City, totaling 86 students and Pesantren Al-Fath Kendari totaling 58 students, so the population in this study was 144. Result: The results of this study using Mann-Whitney test showed that the effect of counselingon student’s knowledge (p-value = 0,007< 0,05). The effect of counseling on student’s attitudes (p-value = 0,000< 0,05). The effect of counseling on student’s and actions (p-value = 0,020< 0,05). Conclusion: There were differences effect of counseling using combination methods of lectures, discussions, practices, and role models on students' knowledge, attitudes, and actionsin preventing caries of the permanent first molars at Hidayatullah Islamic Elementary School Kendari.